Kefir Enriched with Encapsulated Volatile Oils: Investigation of Antimicrobial Activity and Chemical Composition - Mihaela Adriana Tița; Maria Adelina Constantinescu; Tiberius Ilie Opruța; Cristina Bătuşaru; Lăcrămioara Rusu; Ovidiu Tița (Applied Sciences, 2023)
The present study was designed to determine the changes in the chemical composition of kefir enriched with encapsulated volatile oils by enzymatic methods and the antimicrobial activity of volatile oils. Using encapsulated volatile oils (fennel, mint, and lavender) and cow’s milk, we created three different forms of kefir. To highlight the antiseptic capacity of the volatile oils, we performed their antimicrobial analysis on three types of molds (Geotrichum candidum, Penicillium expansum, Aspergillus niger) and one Gram-negative bacterium (Escherichia coli). The technique used to determine antimicrobial activity was Kirby–Bauer. The changes in the chemical composition of kefir samples with encapsulated volatile oils were analyzed using enzymatic methods and were compared with a control sample of kefir. The main analyzed chemical compounds were lactose, D-glucose, D-galactose, acetic acid, ethanol, L-lactic acid, and L-glutamic acid. The kefir samples enriched with volatile oils obtained superior results compared to the control sample during the whole analysis period. The main advantage of using encapsulation is that the bioactive compounds of the volatile oils are gradually released in the kefir sample due to the protection provided by sodium alginate. As a result, products with high nutritional values were obtained that are beneficial to the consumer’s health and have a longer shelf life thanks to the volatile oils’ antimicrobial properties.